A mobility model for a tethered skidder. Issue 3 (2nd September 2022) - Sessions, John; Wimer, Jeffrey
ABSTRACT: Tethered logging has been rapidly increasing in popularity in many regions following developments in Europe and New Zealand. The main application in Europe has focused on using an integral winch to assist harvesters and forwarders. In New Zealand, the application has focused on a remote winch to stabilize and assist a feller-buncher, permitting cutting and bunching of whole trees for extraction by cable yarding, or in some cases shovel logging. In areas where cable yarding equipment is not available, a tethered skidder could be an alternative for moving bunched trees from the field to roadside, or in steep areas with convex slopes to avoid the use of intermediate supports. As a model for estimating the performance of the tethered skidder is not available, the purpose of this manuscript is to present a preliminary model. A methodology for a six-wheel drive tethered skidder is developed by extending existing non-tethered four-wheel drive skidder models for extraction uphill in steep terrain. The load that can be skidded is a function of skidder weight, soil strength, and tether tension. Tire inflation pressure is also an important variable. The energy intensity of tethered skidders is much higher than for cable logging due to the weight of the skidder. The lighter the skidder, the lower the power requirements and the lower the energy intensity.